Molecular and electronic structure of terminal and alkali metal-capped uranium(V) nitride complexes - David M. King (Nature Portfolio, 2016)
Actinide electronic structure determination is fundamentally challenging. Here, the authors assemble a family of uranium(V)-nitrides and quantify the electronic structure of the molecules, defining the relative importance of spin orbit coupling and crystal field interactions.